Differences Between Teachers’ and Parents’ Perspectives on Character Education in Schools in the Community of Madrid - Fernández-Espinosa, Verónica; Redondo-Corcobado, Paloma; Velázquez Gil, Marta (British Journal of Educational Studies, 2026)
This study analyses the differences and similarities between the perspectives of teachers and parents in the Community of Madrid regarding Character Education (CE) in schools. Using a mixed-methods design combining quantitative questionnaires and an open-ended question, data were collected from 444 teachers and 1020 parents. The results reveal a highly positive evaluation of CE by both groups, who agree on its importance for students’ holistic development and its positive influence on academic performance. However, differences emerged regarding the attribution of responsibility, the prioritisation of virtues, and the perceived importance of CE compared to academic achievement. Additionally, few parents expressed concerns about potential ideological bias in the implementation of CE. The study concludes by highlighting the need for an educational alliance between teachers and parents grounded in shared language and co-responsibility, and the importance of revaluing relational virtues such as compassion to foster more inclusive and just educational communities.
Keywords: character education; virtues; parents; school; educational alliance; human flourishing